2019
DOI: 10.1039/c9dt03574e
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids with polychloride anions as effective oxidants for the dissolution of UO2

Abstract: Polychloride ionic liquids can not only successfully dissolve UO2, but also raise the chlorine efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
1
8
0
2
Order By: Relevance
“…[OMIM] 2 [SnBr 6 ] ( O h ) was synthesized and characterized by Raman and NMR spectroscopy. The 119 Sn NMR in DCM at δ = −2060 ppm as well as the Raman spectra at 205, 182, and 135 cm –1 fit well to previous literature values. ,,, …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…[OMIM] 2 [SnBr 6 ] ( O h ) was synthesized and characterized by Raman and NMR spectroscopy. The 119 Sn NMR in DCM at δ = −2060 ppm as well as the Raman spectra at 205, 182, and 135 cm –1 fit well to previous literature values. ,,, …”
Section: Resultssupporting
confidence: 89%
“…Recently, this class of ILs has been studied electrochemically . Furthermore, it can be shown that these different trihalogen monoanions dissolve a variety of precious metals, by forming halogenidometallates which can therefore be used, e.g., for metal recycling purposes. ,, However, in these important studies, unfortunately no structural analysis confirming the resulting metalate substances had been undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, we found that [NEt 3 Me]­[Cl 3 ] can directly react with CO, without further activation by light or heat, to form phosgene (COCl 2 ), a major intermediate in the synthesis of polyurethanes and polycarbonates . Additionally, trichloride ionic liquids are useful for the oxidative dissolution of metals and alloys for metal recycling applications, as demonstrated by the group of Binnemans and others. …”
Section: Introductionmentioning
confidence: 99%
“…Chu und Mitarbeiter verwendeten 1‐Butyl‐3‐methylimidazoliumtrichlorid ([Bmim][Cl 3 ]), um Urandioxid (UO 2 ), einen wichtigen Bestandteil von Kernbrennstoffen, zu lösen, wobei in der ionischen Flüssigkeit [Bmim] 2 [UO 2 Cl 4 ] gebildet wird. Werden Gemische aus Urandioxid und Lanthanidoxiden in [Bmim][Cl 3 ] gelöst, wird eine selektive Kristallisation von [Bmim] 2 [UO 2 Cl 4 ] beobachtet, die die Trennung von Uran und Lanthaniden ermöglicht [40] …”
Section: Die Reaktivität Von Trichloridenunclassified